Cytotoxicity of catechol towards human glioblastoma cells via superoxide and reactive quinones generation - Pereira,Marco Roberto Guimarães (2004)
It is known that the exposure to benzene in the petroleum industry causes lympho-haematopoietic cancer among workers. However, there is little data concerning the toxicity of benzene to the central nervous system. Benzene easily penetrates the brain where it is metabolized to catechol. Since catechol autoxidizes in physiological phosphate buffer, we hypothesized that it could be toxic towards glial cells due to the generation of reactive oxygen species and quinones. In this work we studied the cytotoxic properties of catechol towards human glioblastoma cells. We found that catechol was toxic towards these cells after 72 hours and this toxicity was related to the formation of quinones. Catechol at 230µM killed 50% of cells. The catechol-induced cytotoxicity was prevented by the addition of 100U superoxide dismutase, which also inhibited the formation of quinones. These data suggest that catechol induces cytotoxicity via the extracellular generation of superoxide and quinones.